Screening of the whole human cytochrome P450 complement (CYPome) with enzyme bag cocktails - Sangeeta Shrestha Sharma; Shishir Sharma; Matthias Bureik (Elsevier, 2020)
We have previously introduced the use of permeabilized fission yeast cells (enzyme bags) that recombinantly express full-length CYPs for drug metabolism studies. Such enzyme bags are cells with pores that function as enzymes in situ. They can easily be prepared without a need for ultracentrifugation and may be used in similar protocols as microsomes. In this study we report the preparation of enzyme bag cocktails that permit the testing of multiple CYPs in a single enzyme bag reaction. Moreover, we established a convenient testing scheme that permits a rapid screen of all human CYPs for activity towards any given candidate substrate. An important aspect of this approach is the reduction of individual CYP test assays. If a cocktail containing many CYPs tests negative, it follows that all CYPs included in that cocktail need not be tested individually, thus saving time and resources. The new protocol was validated using two probe substrates.